Uprooted : Race, Public Housing, and the Archaeology of Four Lost New Orleans Neighborhoods - Gray, D. Ryan (Danny Ryan), 1973- (Book collections on Project MUSE., 2020)
"This book is an archaeological investigation of four New Orleans neighborhoods that were replaced by public housing projects around World War II. Each of these neighborhoods was identified as a "slum" historically, but the material record challenges the simplicity of this designation. Gray provides evidence of the inventiveness of former residents who were marginalized by class, color, or gender, whose everyday strategies of survival, subsistence, and spirituality challenged the city's developing racial and social hierarchies. Slum clearance at the national scale was a form of erasure, in which whole neighborhoods and their all-too-complicated realities were obliterated from the built environment of cities across the United Sates. In New Orleans, from the St. Thomas Housing Project, which replaced the working-class riverfront Irish Channel, to Iberville, constructed over what remained of the Storyville red light district, the logics of clearance inevitably revolved around the complexities of race. This work uses both documents and archaeological data to examine what this entailed at a variety of scales, reconstructing narratives of the households and communities affected by clearance. Public housing, both in New Orleans and elsewhere, imposed a new kind of control on urban life that had the effect of making cities both more segregated and more unequal. The story of the neighborhoods that were destroyed provides a reminder that this was not an inevitable outcome, and that a more equitable and just city is still possible today"--